Improving Teachers’ Competence in Designing Contextual STEM-Based Learning Activities through Training and Mentoring - Ika Hesti Agustin; Dafik; Marsidi; Kiswara Agung Santoso; Kusbudiono (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
The development of twenty-first-century competencies requires teachers to design contextual and problem-oriented learning activities. However, many teachers still face difficulties in translating STEM concepts into practical classroom activities. This community service program aimed to improve teachers’ competence in designing contextual STEM-based learning activities through training and mentoring. The program was conducted at CDAST, University of Jember, from February to March 2026, involving 25 teachers from various subject areas. The activities included needs identification, preparation of materials and templates, delivery of STEM concepts, demonstration of simple STEM activities, group workshops, mentoring, presentation, and evaluation. Data were collected through observation, questionnaires, and product assessment using a rubric. The results showed that participants produced five STEM Learning Activity designs. Participant responses were highly positive, with all indicators exceeding 90%, while product assessment scores ranged from 2.60 to 2.80 on a three-point scale. These findings indicate that practice-based training and mentoring effectively support teachers in developing applicable STEM learning designs.